A long voyage to the moon : the life of naval aviator and Apollo 17 astronaut Ron Evans - Bowman, Geoffrey (Geoffrey Alexander) (Outward odyssey : a people's history of spaceflight, 2021)
Biography of Apollo 17 astronaut Ron Evans (1933-1990).